2063. Extracellular Release of β-Lactamase Is Responsible for the Cefazolin Inoculum Effect (CzIE) in Methicillin-Susceptible Staphylococcus aureus. (26th November 2018) - Carvajal, Lina P; Santiago, Alec; Echeverri, Aura; Rios, Rafael; Rincon, Sandra; Panesso, Diana; Diaz, Lorena; Miller, William; Sun, Zhizheng; Palzkill, Timothy; Arias, Cesar; Reyes, Jinnethe
Abstract: Background: Cefazolin is becoming first-line therapy for MSSA infections since it appears to be better tolerated than isoxazolyl penicillins with similar outcomes. An important concern when using cephalosporins as first-line therapy for MSSA is the CzIE, defined as MICs ≥ 16 µg/mL when performed at high bacterial inoculum (~10 7 CFU/mL) compared with standard inoculum (~10 5 CFU/mL). We postulated that release of BlaZ (a lipoprotein) to the extracellular milieu is the mechanism responsible for the CzIE. Confirmation of this phenomenon would permit developing a rapid test to identify this phenomenon in clinical settings. Methods: We monitored the hydrolysis of 50 μM of nitrocefin by S. aur eus supernatants after induction with ampicillin (150 µg/mL) for 1 h. A total of 150 μL of supernatants (after centrifugation) was incubated with 50 μM nitrocefin at 25°C in 20 mM HEPES, pH 7.4, 100 mM NaCl for 30 minutes. Nitrocefin hydrolysis was monitored by following the change in absorbance at 482 resulting from opening of the β-lactam ring of nitrocefin. Visual inspection to monitor color changes was also performed. We initially used 3 strains of MSSA, (i) S. aureus TX0117, a well-characterized strain that exhibits the CzIE; (ii) TX0117c, a derivative of TX0117 that harbors a mutation inactivating BlaZ and abolishing the CzIE, and (iii) ATCC 29213 a BlaZ-positive strain that lacks the CzIE. Subsequently, we validated the methodology in 10 South American isolates of different backgrounds that had been previously characterized for the CZIE. Results: A statistically significant difference in ODs after 30 minutes was observed in TX0117 (CzIE) vs. TX0117c (no CzIE) and ATCC 29213 (no CzIE) (all P < 0.001), suggesting high BlaZ activity in supernatants of TX0117 and supporting the release of the enzyme as the main mechanism of the CzIE. All South American isolates that exhibited the CzIE were identified by the nitrocefin assay. Of note, isolates producing Type C BlaZ gave a weaker reaction, although still significantly different from isolates without the CzIE. Hydrolysis of nitrocefin was also readily detectable by visual inspection. Conclusion: The CzIE is likely due to release of BlaZ to the extracellular milieu. A rapid test that can readily identify MSSA strains exhibiting the CzIE is feasible. Disclosures: W. Miller, Merck: Investigator, Research support. C. Arias, Merck & Co., Inc.: Grant Investigator, Research support; MeMed: Grant Investigator, Research support; Allergan: Grant Investigator, Research support.